3D Printing of New Foods Using Cellulose-Based Gels Obtained from Cerotonia siliqua L. Byproducts - Antoni Capellà; Mónica Umaña; Esperanza Dalmau; Juan A. Cárcel; Antoni Femenia (Gels)
Carob pulp is a valuable source of cellulose-rich fraction (CRF) for many food applications. This study aimed to obtain and characterize a CRF derived from carob pulp waste after sugar removal and to evaluate its potential use in the 3D printing of cellulose-rich foods. Thus, the extraction of the CRF present in carob pulp (by obtaining the alcohol-insoluble residue) was carried out, accounting for nearly 45% dm (dry matter) of this byproduct. The CRF contained about 24% dm of cellulose. The functional properties (swelling capacity, water retention, and fat adsorption) related to this fraction were determined, showing a value of 5.9 mL/g of CRF and 4.0 and 6.5 g/g of CRF, respectively. Different gels were formulated with a total solids content of 15% wm (wet matter), using potato peel flour as a base and partially substituting with CRF (0% to 8% wm). The cellulose-based gels were characterized in terms of viscosity, water distribution (low-field Nuclear Magnetic Resonance), and printability, while the 3D printed samples were assessed for their textural properties. As the percentage of added CRF increased, the viscosity decreased while the water retention increased. Printability improved when small proportions of CRF (2% to 4%) were used, while it deteriorated for higher percentages (6% to 8%). The textural properties (hardness, adhesiveness, cohesiveness, and gumminess) showed significant changes caused by the addition of CRF, with gels containing 3% to 4% CRF exhibiting the most suitable printing values. In summary, this study demonstrates the significant potential of carob cellulose-based gel as an ingredient in the 3D printing of novel fiber-rich foods, contributing to reducing food waste and promoting sustainable practices within the framework of the circular economy.